2004
DOI: 10.1021/ja031724o
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Structure of Jadomycin B and the Amino Acid Incorporation Step of Its Biosynthesis

Abstract: Jadomycin B, an antifungal antibiotic with a unique 8H-benz[b]oxazolo[3,2-f]phenanthridine pentacyclic skeleton produced by the bacterium Streptomyces venezuelae ISP 5230, exists in a dynamic equilibrium of two diastereomers differing in the configuration of C-3a. Several novel jadomycins with various amino acid-derived 1-side chains could be generated, by replacing isoleucine in the production medium of S. venezuelae with other amino acids. These two findings led to the conclusion that a nonenzymatic reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
90
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 10 publications
8
90
0
Order By: Relevance
“…33−35 When subjected to shock conditions (ethanol), the bacteria switches natural product production to JdDS (structure found in Figure 2B). 36,37 We have found that this compound is produced at higher levels than is JdB, allowing for straightforward detection by LC-MS/MS analysis. All three strains were successful in utilizing the D-serine minimal media as a nutrient source, growing to comparable OD 600 values ( Figure 1B).…”
Section: ■ Introductionmentioning
confidence: 97%
“…33−35 When subjected to shock conditions (ethanol), the bacteria switches natural product production to JdDS (structure found in Figure 2B). 36,37 We have found that this compound is produced at higher levels than is JdB, allowing for straightforward detection by LC-MS/MS analysis. All three strains were successful in utilizing the D-serine minimal media as a nutrient source, growing to comparable OD 600 values ( Figure 1B).…”
Section: ■ Introductionmentioning
confidence: 97%
“…The phenanthridine ring system is plausibly derived by condensation of an amino acid with the postulated acid/ aldehyde intermediate (5), formed during angucyclic ring opening (7,9). Strengthening this possibility is the formation of jadomycin analogues when different amino acids are supplied as precursors (10,11). Until now, the only oxygenase gene identified in the jad biosynthetic cluster (Fig.…”
mentioning
confidence: 99%
“…As we have reported [10], by directed biosynthesis eleven new jadomycins were produced. Five of them including compounds 2, 3, 4, 5, and 6 were characterized by NMR.…”
mentioning
confidence: 86%
“…During its biosynthesis, an angucyclinone intermediate undergoes oxidative cleavage at ring B and an L-isoleucine is incorporated to generate the unique pentacyclic core of the jadomycin aglycon [8,9]. By substituting L-isoleucine in the jadomycin B production medium with other amino acids, eleven new jadomycin derivatives were generated [10]. Five of them ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation